2023
DOI: 10.1186/s13047-023-00672-6
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐professional survey of UK practice in the use of intra‐articular corticosteroid injection for symptomatic first metatarsophalangeal joint osteoarthritis

Michael R. Backhouse,
Jill Halstead,
Edward Roddy
et al.

Abstract: Background The first metatarsophalangeal joint is the most common site of osteoarthritis (OA) in the foot and ankle. Intra-articular corticosteroid injections are widely used for this condition, but little is known about their use in practice. This study explored current practice within the UK National Health Service (NHS) relating to the administration of intra-articular corticosteroids for people with painful first metatarsophalangeal joint (MTPJ) OA. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Backhouse, MR et al (2023) 7 showed Multiple professional groups regularly administer intra-articular corticosteroids for symptomatic first MTPJ OA across a range of NHS healthcare settings. Overall, methylprednisolone acetate was the most commonly administered steroid and lidocaine hydrochloride the most common local anaesthetic.…”
Section: Resultsmentioning
confidence: 99%
“…Backhouse, MR et al (2023) 7 showed Multiple professional groups regularly administer intra-articular corticosteroids for symptomatic first MTPJ OA across a range of NHS healthcare settings. Overall, methylprednisolone acetate was the most commonly administered steroid and lidocaine hydrochloride the most common local anaesthetic.…”
Section: Resultsmentioning
confidence: 99%
“…The survey was open for a 6‐week period (23 October 2023 to 04 December 2023). This timeframe was selected based on similar studies and to allow sufficient time for delays in publishing and distribution by national associations [ 12 , 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%